KONTRIBUSI KEKUATAN OTOT LENGAN DAN KOORDINASI MATA TANGAN TERHADAP KEMAMPUAN SERVIS ATAS BOLAVOLI PADA PEMAIN EKSTRAKURIKULER SMK NEGERI 1 SUNGAI APIT KABUPATEN SIAK - Naufal Marwan, Muhammad; Apriani, Leni; Alpen, Joni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Observations made inside the subject at some stage in extracurricular sports for students of SMK Negeri 1 Sungai Apit Siak Regency confirmed that a few college students had not mastered the simple techniques of volleyball, along with the top serve. The unique objective of this study become to decide the correlation among the volleyball service ability of extracurricular college students at Sungai Apit 1 Vocational middle college and the coordination of arm and eye muscle energy. This studies is dating research, and the sample includes 12 extracurricular college students. Arm muscle electricity, hand eye coordination, and volleyball carrier ability are the three variables used in this observe. The consequences of the examine show that the primary hypothesis has a contribution of arm muscle power of 37.21% to upper serve competencies, the usage of rcount = zero.sixty one and rtable = zero.576. This shows that the power of the participant's arm muscular tissues contributes to the electricity expended while hitting the served ball. the use of rcount = 0.56 and rtable = zero.532, the second one speculation also states that the contribution of hand eye coordination to top serving capabilities is 31.36%. for this reason, based on this examine, it's far clear that players can direct the served ball the use of their hand-eye coordination. this example is inspired by using college students who've now not been able to have correct top serve accuracy capabilities. the level of arm muscle strength of students tends to have higher abilties supported via their characteristics which might be used to creating hand movements, of route the palms have relative resistance and power.